John Chrysostom’s Commentary on the Collection for Jerusalem in Rom 15:25–32 - Widodo, Agus; Aryanto, Antonius Galih Arga Wiwin (Verbum Vitae, 2022)
John Chrysostom (349–407) provides the most comprehensive commentary on the Pauline epistles from the patristic era. During his priestly mission in Antioch (386–397) and his episcopate in Constantinople (398–403), he wrote over 200 homiletic commentaries on the entire Pauline epistolary body of work. This research attempts to analyze how Chrysostom interprets Paul’s verses concerning the collection and uses them to organize and transform the ecclesial groups into communities of love, particularly paying attention to the poor. The study focuses on the works of John Chrysostom on Rom 15:25–29. Based on his interpretation, the status of debtors in the spiritual blessings is the main reason why the Romans had to be more earnest in almsgiving, imitating the Macedonians and the Achaeans who had helped the community in Jerusalem. He also encourages them to reform their lives, cutting off the superfluities, luxurious lifestyles, and bad attitudes in squandering money on other selfish needs. At the same time, he stirrers them up to meet their needs moderately, which meant using only the goods that are truly necessary for a healthy and dignified life so that they would always have something to share with the poor.